2008
DOI: 10.1002/ab.20272
|View full text |Cite
|
Sign up to set email alerts
|

Are the effects of Unreal violent video games pronounced when playing with a virtual reality system?

Abstract: This study was conducted to analyze the short‐term effects of violent electronic games, played with or without a virtual reality (VR) device, on the instigation of aggressive behavior. Physiological arousal (heart rate (HR)), priming of aggressive thoughts, and state hostility were also measured to test their possible mediation on the relationship between playing the violent game (VG) and aggression. The participants—148 undergraduate students—were randomly assigned to four treatment conditions: two groups pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 49 publications
2
30
1
Order By: Relevance
“…The relationship between violent content and aggression has also been demonstrated in VR, with findings having shown that exposure to violent VR can lead to elevated levels of aggression (Calvert and Tan 1994) and hostile thoughts (Tomborini, Eastin, Skalski, Lachlan, Fediuk and Brady 2004). However, while researchers have attempted to determine whether VR has greater potential to elicit higher levels of aggression compared to 2D video games, empirical support for this hypothesis is still lacking (Arriaga et al 2008;Eastin and Griffiths 2006).…”
Section: The Potential Side Effects Of Playing Video Gamesmentioning
confidence: 99%
“…The relationship between violent content and aggression has also been demonstrated in VR, with findings having shown that exposure to violent VR can lead to elevated levels of aggression (Calvert and Tan 1994) and hostile thoughts (Tomborini, Eastin, Skalski, Lachlan, Fediuk and Brady 2004). However, while researchers have attempted to determine whether VR has greater potential to elicit higher levels of aggression compared to 2D video games, empirical support for this hypothesis is still lacking (Arriaga et al 2008;Eastin and Griffiths 2006).…”
Section: The Potential Side Effects Of Playing Video Gamesmentioning
confidence: 99%
“…Arterial blood pressure in the control arm was measured using the oscillometric or auscultatory (Korotkoff sounds) plethysmographic technique with a TSD120 pressure transducer connected the computerized MP150‐BIOPAC data acquisition system via to a DA100C amplifier (BIOPAC Systems, Goleta, CA, USA) 9–11. The cuff was inflated to and held at 70 mmHg pressure to prevent venous pooling, thus avoiding veno‐arteriolar reflex vasoconstriction.…”
Section: Methodsmentioning
confidence: 99%
“…Arterial blood pressure in the control arm was measured using the oscillometric or auscultatory (Korotkoff sounds) plethysmographic technique with a TSD120 pressure transducer connected the computerized MP150-BIOPAC data acquisition system via to a DA100C amplifier (BIOPAC Systems, Goleta, CA, USA). [9][10][11] The cuff was inflated to and held at 70 mmHg pressure to prevent venous pooling, thus avoiding veno-arteriolar reflex vasoconstriction. Pulsatile volume changes of the brachial artery induce a pressure alteration in the cuff, which is sensed by the pressure transducer, and then transmitted, amplified and recorded by the BIOPAC acquisition system.…”
Section: Biopac System Measurementsmentioning
confidence: 99%
“…The author found that the stereoscopic monitor elicits stronger emotions and a sense of presence. Similarly, Arriaga et al 24 reported a significant increase in participants' physiological arousal playing video games on a VR system compared to its desktop-based counterpart. Persky and Blascovich 25 observed not only the same arousal but also an increase in feelings of aggression.…”
Section: Introductionmentioning
confidence: 92%